Influence of Large Steric Hinderance Substituent Position on Conformation and Charge Transfer Process for Non‐Fused Ring Acceptors. Issue 4 (25th February 2022) - Li, Jiayao; Li, Hao; Ma, Lijiao; Xu, Ye; Cui, Yong; Wang, Jingwen; Ren, Junzhen; Zhu, Jincheng; Zhang, Shaoqing; Hou, Jianhui
Abstract: To obtain stable and planar molecular geometry in non‐fused electron acceptors, A4T‐25 and A4T‐26 are designed and synthesized by introducing the bulk 2, 4, 6‐triisopropylphenyl side groups onto different positions of the central two thiophene units. A4T‐25 and A4T‐26 both show a narrow‐bandgap of 1.39 and 1.46 eV, with highest occupied molecular orbital/lowest unoccupied molecular orbital levels of −5.56/−3.81 and −5.65/−3.83 eV, respectively, and the electrostatic potential distributions imply that they have strong electron‐accepting capability. The single crystal structure analysis and the transfer integral calculation demonstrate that the much more compact π‐π stacking in A4T‐26 can promote efficient charge transportation compared to that in A4T‐25. Therefore, the electron mobility of A4T‐26 is obviously higher and more balanced than that of A4T‐25. When blending the two acceptors with the same polymer donor PBDB‐TF, the photovoltaic cell based on PBDB‐TF:A4T‐25 has an inadequate power conversion efficiency (PCE) of 7.83%, while the PBDB‐TF:A4T‐26‐based one yields an enhanced PCE of 12.1%. Overall, this study offers an insight into the relationship between the fine‐tuning of the molecular structure of non‐fused ring acceptors and the corresponding charge transfer process in organic solar cells. Abstract : Functional groups with large steric hindrance can effectively stabilize the molecular conformation of non‐fused acceptors. When they are introduced into different locations, the non‐fused acceptors, A4T‐25 and A4T‐26, show significant aggregation behavior and charge transport property in organic solar cells.